Diverticular disease is associated with benign intra-abdominal cystic disease. (4th May 2017) - Wrafter, Paula F.; Connelly, Tara M.; Khan, Jody S. A.; Lucey, Brian C.; Berg, Arthur; Koltun, Walter; Joyce, William P.
ABSTRACT: Background : Diverticular disease (DD) and hepatic and renal cysts have been linked with defects in collagen and dysfunctional matrix metalloproteinases. Methods: Consecutive abdominal computed tomography scans between January-July 2015 were prospectively studied to determine a correlation between visceral cysts and DD. Patients with a sigmoid colectomy for pathology other than DD and scans in which DD and/or solid organs were not fully visualized were excluded. A subgroup analysis was performed on youthful DD patients (<55 years of age, n = 32) vs. older controls (>55, n = 213). Results : 238 DD patients (50.8% male) and 369 controls (40.5% male, p = .02) were included. Incidence of visceral cystic disease in DD patients vs. controls was 71.4% vs. 22.5% (p < 0.00001). Renal cysts, present in 53.4% of the DD patients and 18.7% of the controls (p < .00001), were more common than hepatic cysts in both groups. Hepatic cyst prevalence was 8.8 vs. 2.4% (p = .0008). In the subgroup analysis, cystic disease was present in 56.2% of youthful DD patients vs. 29.1% of older controls (p = .004). Conclusions: A significant association between cystic disease and DD was demonstrated overall and in subgroup analysis inclusive of youthful DD patients and older controls. These findings suggest a global defect in connective tissue integrity in DD patients.